Solid-phase glycan isolation for glycomics analysis - Yang, Shuang (2012)
Glycosylation is one of the most significant protein PTMs. The biological activities of proteins are dramatically changed by the glycans associated with them. Thus, structural analysis of the glycans of glycoproteins in complex biological or clinical samples is critical in correlation with the functions of glycans with diseases. Profiling of glycans by HPLC-MS is a commonly used technique in analyzing glycan structures and quantifying their relative abundance in different biological systems. Methods relied on MS require isolation of glycans from negligible salts and other contaminant ions since salts and ions may interfere with the glycans, resulting in poor glycan ionization. To accomplish those objectives, glycan isolation and clean-up methods including SPE, liquid-phase extraction, chromatography, and electrophoresis have been developed. Traditionally, glycans are isolated from proteins or peptides using a combination of hydrophobic and hydrophilic columns: proteins and peptides remain on hydrophobic absorbent while glycans, salts, and other hydrophilic reagents are collected as flowthrough. The glycans in the flowthrough are then purified through graphite-activated carbon column by hydrophilic interaction LC. Yet, the drawback in these affinity-based approaches is nonspecific binding. As a result, chemical methods by hydrazide or oxime have been developed for solid-phase isolation of glycans with high specificity and yield. Combined with high-resolution MS, specific glycan isolation techniques provide tremendous potentials as useful tools for glycomics analysis.